2008
DOI: 10.1103/physrevb.77.094415
|View full text |Cite
|
Sign up to set email alerts
|

Critical lines and massive phases in quantum spin ladders with dimerization

Abstract: We determine the existence of critical lines in dimerized quantum spin ladders in their phase diagram of coupling constants using the finite-size DMRG algorithm. We consider both staggered and columnar dimerization patterns, and antiferromagnetic and ferromagnetic inter-leg couplings. The existence of critical phases depends on the precise combination of these patterns. The nature of the massive phases separating the critical lines are characterized with generalized string order parameters that determine their… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
4
18
0
Order By: Relevance
“…As we shall see, the phase transitions of the dimerized spin chains disappear before reaching the spin ladder geometry, in agreement with previous results, 7,8,[10][11][12]15,27 but some traces of these phase transitions can still be found in the rung Berry phases of the ladder, suggesting the presence of a series of 2S crossovers in spin-S ladders.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…As we shall see, the phase transitions of the dimerized spin chains disappear before reaching the spin ladder geometry, in agreement with previous results, 7,8,[10][11][12]15,27 but some traces of these phase transitions can still be found in the rung Berry phases of the ladder, suggesting the presence of a series of 2S crossovers in spin-S ladders.…”
Section: Introductionsupporting
confidence: 93%
“…6 In recent years the investigation of the topological properties of other models of quantum magnetism, in particular spin-1/2 ladders, has been a very active field of research. [7][8][9][10][11][12][13][14][15][16][17] A few years ago, Hatsugai proposed an alternative characterization of quantum magnets in terms of a Berry phase defined by twisting the XY components of the spin-spin interaction of one or several local bonds. 18,19 He showed that, if the system has time-reversal symmetry, this Berry phase is quantized and can only take the values 0 or π (mod 2π ), and that some phase transitions can be characterized by a change of Berry phase.…”
Section: Introductionmentioning
confidence: 99%
“…General (m, n)-VBS states belong to a class of spin liquids which are known to possess an special hidden order that can be identified by a particular non-local order parameter called the string order parameter (SOP) [22,23,24,25,26,27]. This order parameter has proved itself extremely successful in the task of characterizing diverse kinds of such states, both in the pure one dimensional cases and also in less trivial systems such as ladders [25], [27]. We shall see that this parameter also allows us to characterize the Cr8Ni ground state.…”
Section: Figmentioning
confidence: 99%
“…Analytical methods have been applied to uncover this rich phase structure, some of them non-perturbative [1,6,7,8,9]. However, they are not sufficient to study with enough precision the whole range of coupling parameters entering in their quantum lattice Hamiltonians and, consequently, they have to be complemented with numerical studies [10,11,12,13], which sometimes modify the conclusions achieved with analytical methods, either quantitative and/or qualitatively.…”
Section: Introductionmentioning
confidence: 99%